Sucesión de la estructura vegetal y su influencia en la diversidad florística en el bosque protector murocomba. Año 2015 - Gomezcoello Zúñiga, Héctor Avelino (2016)
The horizontal and vertical structure of three successional forests in the Protected Forest Murocomba, canton Valencia, province of Los Rios. This research was conducted in a farm with an area of 44.7774 ha, whose UTM coordinates WGS 84 Zone 17 South are: North 705,072 E; 9930608 N, Southeast 705,072 E; 9930608 N, Southwest 705,026 E; 9929628 N, at an altitude between 200 and 800 mosl. Three substrates with three unit samples were taken. The first was located at 420 mosl, the substrate 2 to 493 mosl and the third at 586 mosl. Each sample unit measuring 400 m2. Dasometric information considering the characteristics, scientific name, common name and family of all individuals (trees), according to the modified by Villavicencio and Valdez (2003) registered design. A total of 33 families, 92 species and 996 individuals were recorded, being the Asteraceae, Euphorbiaceae, Arecaceae Melastomataceae families the most representatives. The species that showed higher absolute abundance of the 92 registered are: Iriartea deltoidea Ruiz & Pav with 72 individuals, 66 individuals Baccharis sp Acalypha diversifolia Jacq and 56 individuals. The index more representative Value for successional Forests Importance was obtained for species Baccharis sp. for the formation of forest regeneration with a total of 174.45%, Wettinia quinaria (Cook & Doyle O.F.) Burret a total of 122.80% and Cuatresia cf. Harlingiana Hunz with 115.36% for the formation of secondary forest with minimal intervention. The values Shannon diversity within nine sampling units exposed the existence of an average diversity, being the 2UM2 and 3UM3 units which recorded the highest values (3.188) and (3.365), unlike the unit 1UM2 which he recorded a rate of 2,411. The percentage of similarity between the sample units does not exceed 34.80%. The cluster analysis revealed two distinct groups in the sampling units, which differentiate according to the type of forest temporary formation.